Perawatan bedah ortognati pada maloklusi dentoskeletal kelas III dengan asimetri wajah dan canting oklusal rahang atasOrthognathic surgical treatment of class III dentoskeletal malocclusion with facial asymmetry and maxillary occlusal cant - Endah Mardiati; Ida Ayu Astuti (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2021)
Pendahuluan: Asimetri wajah akibat canting oklusal rahang atas seringkali menjadi keluhan  estetika wajah pasien. Perawatan canting oklusal parah memerlukan kombinasi perawatan ortodonti cekat dengan bedah ortognati. Tujuan laporan kasus ini adalah untuk menjelaskan perawatan ortodonti cekat kombinasi bedah Le Fort 1 pada kasus canting oklusal rahang atas pada maloklusi dentoskeletal kelas III disertai asimetri wajah. Laporan kasus: Seorang pasien perempuan umur 17 tahun 7 bulan datang ke praktek pribadi dengan keluhan gigi rahang atas miring, gigi belakang kanan tidak dapat mengunyah dengan nyaman. Pasien ingin dirawat gigi dan rahangnya. Pemeriksaan ekstra oral menunjukan wajah asimetri, profil cekung dan dagu sedikit menonjol. Pemeriksaan intra oral,  garis median rahang atas bergeser ke kiri, rahang bawah bergeser ke kanan, crossbite anterior, crossbite posterior unilateral, retrusi gigi anterior rahang atas dan rahang bawah. Analisis sefalometri lateral: maloklusi dentoskeletal kelas III. Diagnosis yang diberikan adalah maloklusi dentoskeletal kelas III disertai canting oklusal rahang atas, wajah asimetri, crossbite anterior, crossbite unilateral posterior. Rencana perawatan adalah perawatan ortodonti cekat kombinasi bedah ortognati Le Fort 1. Perawatan dilakukan dalam 4 tahap yaitu perawatan ortodonti dekompensasi, perawatan bedah ortognati rahang atas, perawatan ortodonti pasca bedah rahang, debonding dan pemasangan retainer. Simpulan: Maloklusi skeletal kelas III disertai canting oklusal rahang atas, asimetri wajah, crossbite anterior, dan crossbite posterior unilateral, yang dirawat menggunakan alat ortodonti cekat dan bedah ortognati Le Fort 1 dapat berhasil dengan baik. Relasi dental dan skeletal tercapai kelas I, interdigitasi gigi rahang atas dan rahang bawah mengunci, fungsi pengunyahan terkoreksi serta pasien merasa sangat puas dengan estetika wajahnya.Kata kunci: Maloklusi skeletal kelas III, asimetri wajah, canting maksila, crossbite anterior, crossbite posterior unilateral, bedah ortognati. ABSTRACTIntroduction: Facial asymmetry due to maxillary occlusal cant often becomes a facial aesthetics complaint. Treatment of severe occlusal cant requires a combination of fixed orthodontic treatment with orthognathic surgery. This case report was aimed to describe the combined fixed orthodontic treatment of Le Fort 1 in maxillary occlusal cant of class III dentoskeletal malocclusion with facial asymmetry. Case report: A female patient aged 17 years seven months came to the private clinic, complained of oblique maxillary teeth, and the right posterior was unable to masticate comfortably. The patient wants to be treated for her teeth and jaw. Extraoral examination revealed facial asymmetry, sunken profile and slightly protruding chin. The intraoral examination resulted in the maxillary median line that shifted to the left, mandible shifted to the right, anterior crossbite, unilateral posterior crossbite, and retrusion of maxillary and mandibular anterior teeth. The lateral cephalometric analysis resulted in class III dentoskeletal malocclusion. The diagnosis was class III dentoskeletal malocclusion with maxillary occlusal cant, facial asymmetry, anterior crossbite, and posterior unilateral crossbite. The treatment plan was fixed orthodontic treatment combined with Le Fort orthognathic surgery. The treatment was carried out in 4 stages: decompensated orthodontic treatment, maxillary orthodontic treatment, post-orthognathic surgery orthodontic treatment, debonding, and retainer placement. Conclusion: Class III skeletal malocclusion with maxillary occlusal cant, facial asymmetry, anterior crossbite, and the unilateral posterior crossbite was successfully treated with a fixed orthodontic appliance and Le Fort 1 orthognathic surgery. The dental and skeletal relations were achieved for class I, the interdigitation of the maxillary and mandibular teeth was locked, the masticatory function was corrected, and the patient was very satisfied with her facial aesthetics.Keywords: Class III skeletal malocclusion, facial asymmetry, maxillary cant, anterior crossbite, unilateral posterior crossbite, orthognathic surgery.